A methodology for the optimal design of gathering pipeline system in old oilfield during its phased development process. (April 2019) - He, Guoxi; Chen, Di; Liao, Kexi; Sun, Jianfei; Nie, Siming
Graphical abstract: Highlights: Optimization models for phased development of old oilfields are proposed. Manifolds with low efficiency have been improved. The access to new developing region has been considered. Both of investment and reliability are included in the objective function. The sensitivity of economic factors and reliability is discussed. Abstract: In the later period of oil field development, new blocks or filled-in wells would be added to enhance the production capacity during the phased development process and thus some abandoned manifolds, wells and pipelines would be recycled. Hence, a practical and economic scheme to optimize the improvement of pipeline network is necessary. A model aiming at optimization of improved pipeline network layout is proposed considering the newly-tied-in wells, the newly-constructed pipelines, and the newly-developed blocks including wells and metering manifolds. The reliability of the pipeline network and the recycling of the occupied old manifolds and pipelines are also taking into account. Implementing the construction cost and the reliability as objective functions, the models seek to define: the number, location, and capacities of newly-developed manifolds; the affiliation of wells; the number of recycled manifolds, wells, and pipelines; the interconnection between all the workable wells and manifolds. This model is solved by the simulated annealing genetic hybrid algorithm. Two real cases based on two oil fields are given in detail, which includes the optimized topological structure of the pipeline network layout, corresponding pipeline parameters, overall investment and the reliability of the optimized pipeline network. Meanwhile, the sensitivity factors including reliability, investment, upper metering limits of the manifolds are analyzed. In conclusion, the manifolds governing few wells are recycled and new manifolds are set up in the new block. The specifications of new pipelines, phased development costs, and the reliability of the optimized pipeline network are obtained. Thus, this research is able to estimate the investment and reliability when improving the pipeline network and to provide guidance for the management of the whole phased development process of old oilfields.